A Feasibility Study on EARTEST Incorporated - Dimaano, Jed P.; Lazo, Jayme C.; Natividad, Maria Ludisa R. (Diliman, Quezon City College of Engineering, 1996)
This study is about the project feasibility of the EARTEST, Inc. The product of the EARTEST, Inc. is the EARTEST, a PC-based screening audiometer which tests an individual of impairments in hearing. There exists a sufficient gap between the current demand and current supply of the audiometers in the country. This scenario favors the entrance of the venture into the market. The existing gap quantifies a part of the market that can be captured by the product. The market of the audiometers consists primarily of schools and ENT doctors. The market totals 54880. Currently 2% of these are satisfied, but for the first year, target market is 9% of the total demand and this is equal to 4940. In addition, a favorable place in the market awaits the product whit its advantages over current supply, those are higher efficiency and lower price. All of these facts add together to prove the EARTEST to be market feasible. The production of the EARTEST is composed of a series of assembly steps of electronic parts into the circuit board. These production steps are easily done and so as the procurement of the needed materials. The technical study entails that all the necessary components of producing the product are available. The production plant s to be located in Malate, Manila. There is a production process, there are procurable raw materials and manpower resources are available. In total, the project cost amounts to P36,724,333.61. Technically, the project is feasible. The financial study shows an adequate amount of profit the venture business will incur.. Taking all the costs in consideration and comparing it with revenues, the company even on its first year of operation will earn a positive income of P64,603,288.71. However, this profit is projected to decrease by 4% in the succeeding years of operation due to the application of inflation rate of 10% on all manufacturing costs. Yet even so, profits remain positive in all the projected years. Net returns on investments are favorable, thus the business is financially feasible. The EARTEST, Inc. is corporation that is made up of 5 major stockholders. The organization of the company is mainly made up of 36 personnel; theses comprise both the direct and indirect labor. In conclusion, the venture project was found to be feasible.
Feasibility Study
Submitted in partial fulfillment of the course requirements in IE 153 : Project Development and Management
Keywords: EARTEST Incorporated; Audiometry; Hearing aid industry; Participatory monitoring and evaluation (Project management)